ETHNO-GENETIC MARKERS OF ANTIOXIDANT SYSTEM (LITERATURE REVIEW) - L. I. Kolesnikova; T. A. Bairova; O. A. Pervushina (Acta Biomedica Scientifica, 2013)
Oxidative stress plays an important role in the pathogenesis a most of diseases. Important components of protecting cells from oxidative stress are antioxidant enzymes, whose activity is genetically determined, due to the presence in the structure of the alleles of genes. Antioxidant enzymes are characterized by population and individual differences in enzyme activity. The study of genetic variation in the population of the world and the history of the formation of its gene pool is one of the promising areas of modern population genetics. Genetic variability of antioxidant enzymes in the body has recently become the most attractive destination in the pathogenesis of many diseases. Due to the involvement of enzymes in the pathogenesis of antioxidant enzymes social diseases is an important implementation. Comprehensive study of the genetic polymorphisms of genes contributes to the formation of human disease susceptibility. The antioxidant system is of the person a system that blocks the formation of free radicals, highly active oxygen. Under normal physiological conditions, a small amount of oxygen is constantly converted to superoxide anions, hydrogen peroxide and hydroxyl radicals. Excessive production of these radicals is a factor of injury; compensatory mechanism is the antioxidant system. The main component of this system is a network of antioxidant enzymes (AOP): superoxide dismutase (SOD), glutathione peroxidase (GPX), catalase (CAT) and paraoxonase (PON). In this case, the activity of enzymes evolutionarily and genetically programmed to optimize the balance of oxidative processes and the activity of antioxidant defense systems. The purpose of the review is to summarize and discuss the current data on genetic polymorphisms of antioxidant enzymes in certain pathologies, the development of which plays the role of oxidative stress.